Visible materials, invisible meanings: colour-based hierarchies in the Middle Ages - Fachechi, Grazia Maria (2024)
The decision that oversaw the choices of pigments used in medieval artworks was based on multiple criteria. Among these was their economic value, often linked to the greater rarity of the raw material from which the pigments were derived, or to the lower availability on the market. Alongside the economic value, there was also the symbolic value attributed to materials and pigments from a symbolism often rooted in references found in the Holy Scriptures, in exegetical, theological, encyclopedic, or other texts. The case studies presented in this paper, based on works created with different media whose pigments underwent specific archaeometric analyses, show that throughout the Middle Ages, sometimes precise hierarchies were employed in the choice of pigments, and the most precious ones were reserved for the most important figures or the most significant details.